Health literacy of nursing students (Revista Contexto & Saúde, 2025)
Objective: To identify health literacy among nursing undergraduates in their final year of undergraduate studies. Method: This is a cross-sectional study with descriptive analysis and a quantitative approach, using the Health Literacy Questionnaire instrument with nursing undergraduates in the 9th and 10th semesters, between 18 and 60 years old, of both sexes, at a private educational institution in the Federal District. The sample included 67 participants who agreed to participate in the study. Results: The study indicates that more than half of nursing undergraduates are female, have not taken a technical course and are up to 40 years old. The ability to find good information about health and understand it stands out among the potentialities in health literacy, while poor time management for self-care stands out among the weaknesses. Conclusion: This study presents evidence about the health literacy conditions of undergraduates who will be a source of knowledge for different populations in the future due to their understanding and mastery of health literacy. This enables research into new interventions in the academic environment aiming at both professional and educational improvement. A more comprehensive health system with more qualified professionals is essential.
Keywords: Health literacy; Nursing students; Health education